(3MOjbI GdeDefjfs - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs ((3MSf Hf eMeO HGbQ GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3cJGH GdWgGQI hCQcGfg CQHYI GdChd aj GdejGg hGdfXQ ajg aj GdeWdb hGdeVGa (B... (3CeG GdeWdb hgh eG jSJMb GWdGb GdGSe ef ZjQ GVGaI agh WGgQ aj faSg eWgQ dg hdZjQg (B...s
(3BNQgG (B:s
.. (3GdKGdKI EPG Gcd GdeMQe Ch dHS eG jMQe Ydjg dHSg eeG dG JbOjQ ajg HNUhU YGed deG dReg Oe TGI hjSbW GdcaGQI Yf GdfGS hGdLGgd GdG GdbjO aYdjgeG ajg GdcaGQI CjVG (B.. (3Jes
(3JHUQI GdYfhGf (B:s
(3QjGV GdeSGFd GdUZjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3GdPQjYI (B6\ 2425s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis